Search for heavy, long-lived, charged particles with large ionisation energy loss in pp collisions at s $$ \sqrt{s} $$ = 13 TeV using the ATLAS experiment and the full Run 2 dataset - The ATLAS collaboration; G. Aad; B. Abbott; D. C. Abbott; A. Abed Abud; K. Abeling; D. K. Abhayasinghe; S. H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; et al. (Journal of High Energy Physics, 2023)
Abstract This paper presents a search for hypothetical massive, charged, long-lived particles with the ATLAS detector at the LHC using an integrated luminosity of 139 fb −1 of proton–proton collisions at s $$ \sqrt{s} $$ = 13 TeV. These particles are expected to move significantly slower than the speed of light and should be identifiable by their high transverse momenta and anomalously large specific ionisation losses, dE/dx. Trajectories reconstructed solely by the inner tracking system and a dE/dx measurement in the pixel detector layers provide sensitivity to particles with lifetimes down to O $$ \mathcal{O} $$ (1) ns with a mass, measured using the Bethe–Bloch relation, ranging from 100 GeV to 3 TeV. Interpretations for pair-production of R-hadrons, charginos and staus in scenarios of supersymmetry compatible with these particles being long-lived are presented, with mass limits extending considerably beyond those from previous searches in broad ranges of lifetime.